2016
DOI: 10.1177/1461444816671891
|View full text |Cite
|
Sign up to set email alerts
|

Explicating problematic social network sites use: A review of concepts, theoretical frameworks, and future directions for communication theorizing

Abstract: The prevalence of social network sites (SNSs) has sparked a growing interest in understanding the development of problematic SNSs use among adolescents. Yet, this nascent area of research is marked by some deficiencies in existing theoretical paradigms. This article seeks to review the state of research in problematic SNSs use—broadly with a specific focus on adolescents—and identify key areas of research for future scholarly work. First, we summarize the historical and recent developments of media addiction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 90 publications
2
69
0
3
Order By: Relevance
“…Like in many addictions, 11 literature has considered the need to include both external and individual-level influences on adolescents' problematic social network use. 12 In this study, we have considered both aspects, likes, self-esteem, and its interplay, evidencing that rewards in terms of likes is related to problematic use, although its effect is moderated by individuals' self-esteem.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Like in many addictions, 11 literature has considered the need to include both external and individual-level influences on adolescents' problematic social network use. 12 In this study, we have considered both aspects, likes, self-esteem, and its interplay, evidencing that rewards in terms of likes is related to problematic use, although its effect is moderated by individuals' self-esteem.…”
Section: Resultsmentioning
confidence: 93%
“…24 In the same vein, other studies have shown that young people with lower self-esteem reported stronger instant messaging addiction, 25 that self-esteem was related to greater online activity as well as self-promotional content on Facebook, 26 that self-esteem was negatively associated with problematic Internet use in young 27 and adolescents, 28 and that addictive use of social media related to lower self-esteem 15,29 especially in the case of adolescents. 12 Although studies have focused on exploring the direct association of self-esteem with problematic use, there is a lack of studies analyzing the moderating role of self-esteem. As noted by some authors 23 although associations between problematic use and individuals variables are established, the lack of research investigating moderators is apparent.…”
Section: H1mentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for these mixed results might be that it is not the frequency of SM use per se that disrupts sleep and sleep-related parameters, but that the way adolescents experience their SM use influences the relationship between SM and sleep (Lee, Ho, & Lwin, 2016). More specifically, it has been argued that some adolescents experience high levels of stress from using SM (Beyens, Frison, & Eggermont, 2016).…”
mentioning
confidence: 99%
“…This excessive involvement in the internet has been called internet addiction in the past and there were even attempts to include this phenomenon into DSM-5 classification. Currently problematic internet use is what is being considered [1,[19][20][21][22][23]. Apart from the general criticism of this concept concerning excessive pathologisation of everyday life [1,21,24,25], the fact was indicated that the internet is a medium allowing a range of different activities of a highly varied potential level of harm like for example online gambling, pornography or social networks [1,9,26,27].…”
Section: ■ Introductionmentioning
confidence: 99%